2006
DOI: 10.1097/00000542-200605000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Electroencephalographic Approximate Entropy Changes in Healthy Volunteers during Remifentanil Infusion

Abstract: Approximate entropy derived from a parietal montage is appropriate for the assessment of the remifentanil effect on the electroencephalogram.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
56
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(68 citation statements)
references
References 34 publications
11
56
1
Order By: Relevance
“…Remifentanil, an intravenous ultra short-acting opioid, depresses central nervous system (CNS) activity with an increase in the delta band power, and causes beta activation after discontinuation, resulting in a rebound of processed electroencephalographic parameters, such as 95% spectral edge frequency, canonical univariate parameter and electroencephalographic approximate entropy (ApEn) [2,3]. Conventionally, these EEG metrics have been used to characterize the time course of intravenous opioids [2,4,5]. In general, pharmacokinetic (one, two or three compartment mammillary models) and pharmacodynamic models (sigmoid Emax model), linked by an effect-compartment model, have been utilized to derive the blood-brain equilibration rate constant (ke0).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Remifentanil, an intravenous ultra short-acting opioid, depresses central nervous system (CNS) activity with an increase in the delta band power, and causes beta activation after discontinuation, resulting in a rebound of processed electroencephalographic parameters, such as 95% spectral edge frequency, canonical univariate parameter and electroencephalographic approximate entropy (ApEn) [2,3]. Conventionally, these EEG metrics have been used to characterize the time course of intravenous opioids [2,4,5]. In general, pharmacokinetic (one, two or three compartment mammillary models) and pharmacodynamic models (sigmoid Emax model), linked by an effect-compartment model, have been utilized to derive the blood-brain equilibration rate constant (ke0).…”
Section: Introductionmentioning
confidence: 99%
“…We have demonstrated that depression of the CNS activity and rebound during and after remifentanil infusion was well characterized by ApEn and that its baseline stability was more stable [2,3]. However, ApEn is heavily dependent on the record length, requiring time series of 100 or more points [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have demonstrated that LZC and ApEn can distinguish between awake and anaesthetized state of human subjects (Anderson, Barr, 2004, Bruhn, Bouillon, 2003, Ferenets et al , 2006, Ferenets et al , 2007, Hans, Dewandre, 2005, Kumar et al , 2007, Noh et al , 2006, Vakkuri, Yli-Hankala, 2004, Voss et al , 2006, Zhang, Roy, 2001). In sleep research ApEn was statistically significantly lower during Stage IV and higher during wake and REM sleep (Burioka et al , 2005, Papadelis et al , 2007.…”
Section: Clinical Application Of Nda Correlated With Unconsciousnessmentioning
confidence: 99%
“…However, as the oscillations are widely distributed in the brain, the scalp potentials provide distinct information depending on the site of the scalp. Most research on remifentanil and EEG has been performed using one [9] or few electrodes [4,5,10]. Using multiple electrodes distributed over the entire scalp, it is possible to assess the topographical distribution of the brain oscillations.…”
mentioning
confidence: 99%
“…Resting EEG is characterized by brain oscillations present in distinct frequency bands such as delta (0.5-4 Hz), theta (4)(5)(6)(7)(8), alpha (8)(9)(10)(11)(12), beta and gamma reflecting the sum of excitatory and inhibitory post-synaptic activities [8]. However, as the oscillations are widely distributed in the brain, the scalp potentials provide distinct information depending on the site of the scalp.…”
mentioning
confidence: 99%